Towards new beginnings: a global perspective of the human dilemma (New Delhi, 1990)
In Towards New Beginnings, the most eminent scientists, philosophers and authors of the 20th century have brought their brilliance to bear on key issues that face humankind today. Coming from fifteen countries all over the world they have discussed issues such as the imminent nuclear threat, the exploitation of natural resources, the information explosion and its implications, the persistence of economic and spiritual want in the midst of material plenty, the dilemma of human alienation and the need to develop a new awareness among individuals of their membership in an Earth Citizenship. The conference Towards New Beginnings on which this book is based was organised by Indira Gandhi Memorial Trust, with support from the Government of India, for worldwide participation in actively joining hands to help find answers to major questions that face humankind in the last quarter of the 20th Century.
Keywords: Political science